Charletonia rocciai Treat and Flechtmann, 1979 (Trombidiformes: Erythraeidae): larval redescription and new records for Brazil - Bassini-Silva, Ricardo [UNESP] (2022)
The family Erythraeidae has 60 genera worldwide, of which Charletonia Oudemans has 86 described species, only two of which are recorded in Brazil. Here, we redescribe one of these species based on the holotype, Charletonia rocciai Treat and Flechtmann, and newly collected material. The material represents new records from four different localities in São Paulo State and one in Santa Catarina State. In addition, we provide SEM images of the morphological structures to improve the diagnosis and redescription, an updated distribution map, including biological data, and new host-associations of C. rocciai with the following orders of insects, Coleoptera and Thysanoptera, and with an order of Arachnida–Araneae.